Expressão de epimerase de dermatam sulfato em linhagens de câncer de mama - Xavier, Everton Galvao [UNIFESP] (2019)
Breast cancer is one of the most incident cancers in the world population, especially in the female population. Estimates show that more than 1.7 million new cases are registered each year and 522,000 are killed. By the year 2050, more than 3.2 million new cases of this pathology are expected to be registered. Proteoglycans are macromolecules that contain a protein core, to which glycosaminoglycan chains (GAGs) are attached covalently. Dermatan sulfate (DS) is a GAG produced by the epimerization of glucuronic acid from chondroitin sulfate to iduronic acid (IduA) by the enzyme epimerase (epiDS). Several studies have shown that proteoglycans containing DS play an important role in tumorigenic processes. This is mainly due to the flexibility that the presence of IduA confers to the polysaccharide chain, allowing specific interactions with proteins, such as growth factors, among other molecule. Studies also show that EpiDS-1 is highly expressed in many tumors, especially esophageal squamous cell carcinoma. The aim of this study was to analyze the expression of epiDS in cell lines that characterize different types of breast cancer MCF-7 (Luminal A), MDA-MB-231 (Triple Negative) and SKBR-3 (HER2). The gene expression of the enzyme was performed by qPCR and the protein content was analyzed by flow cytometry and immunofluorescence. Cell viability was investigated by MTT assay and GAG profile analyzed by radioactive sulfate labeling and electrophoresis. Our results showed that the SKBR-3 cell line presented a pattern of increased cell viability compared to MCF-7 and MDA-MB231cells. Furthermore, SKBR-3 cells presented higher gene expression of the epiDS enzyme and higher 35S-DS content. Curiously, Immunofluorescence assays with specific epimerase (epiDS) antibodies demonstrated greater labeling in the MCF-7 cell line compared to the other cells. We observed that SKBR-3 cells presented epiDS preferably in the form of vesicles and in the perinuclear compartment, suggesting a location in the Golgi Complex, contrasting with the cytoplasm localization in MCF-7 and MDA-MB231 cells. In these cells, the cytoplasm location of the EpiDS enzyme probably compromised the formation of DS chains, but the core protein was able to be detected by the decorin antibody. Golgispecific labeling confirmed the localization of EpiDS in SKBR-3 cells at the Golgi Complex, evidencing that the location was determinant for the synthesis of dermatan sulfate in this lineage, and possibly the dermatan sulfate plays a decisive role in the cellular viability observed.